Science literacy levels of plant metabolism learning for biology education students - Risanti Dhaniaputri; Erni Angraini (University of Muhammadiyah Malang, 2025)
Scientific literacy is a person's ability to think and behave scientifically, apply scientific knowledge, and make decisions in solving problems in everyday life. Biology students are expected to be able to develop scientific literacy. One of them is in the material of plant metabolism. Understanding the concept of plant metabolism will help students in implementing the concept of biological science in everyday life. This is because biology is a branch of natural science that has the potential and makes a major contribution to solving global problems, such as food, health, social, energy, economic, environmental, and technology. This study aims to see the level of science literacy of biology students on plant metabolism material, which is one of the basic materials for modern biology learning and research in the 21st century. This type of research is descriptive quantitative with a survey method, with respondents of undergraduate students of the Ahmad Dahlan University Biology Education Study Program. The test instruments used were the Scientific Inquiry Literacy Test (SILT) and the Multidimensional Scientific Literacy Test (MSLT). Science Literacy (SL) questions have seven indicators. The question material used in the test instrument is knowledge of photosynthesis, cellular respiration, phytochemical biosynthesis pathways, and implementation of plant metabolism concepts in the fields of health and pharmacology. The findings result showed a significant increase in the seven levels of scientific literacy indicators, where the average post-test score was always higher than the pre-test. Most students were included in the conceptual group. The conclusion of the study was that the fairly high scientific literacy scores at the seven levels indicate that students have understood and internalized the concepts and contents of plant metabolism materials, are able to read, interpret, and analyze data, and know the role and application of plant metabolism processes in the development of the world of health and pharmacology, so it can be said that during the learning process there has been an increase in the science literacy of biology students.